Germany : Financial Sector Assessment Program: Detailed Assessment of Observance on Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2011)
The design of the German banking supervision framework is structurally sound, with a robust legislative and operational framework that largely complies with the Basel Core Principles for effective banking supervision (BCP). Various improvements to the German supervisory framework have been implemented, acting on multiple recommendations and initiating improvements in supervisory practices on the basis of lessons from the global financial crisis. Further efforts are needed to make fully operational the improvements initiated in light of the lessons from the global financial crisis.